(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper focuses on therapeutic gold nanoparticles selective distribution of medicines. In this region nanotechnology has been one of the most exciting innovative research fields. Gold nanoparticles have specific benefits in this field because of their unique properties, small size strong area-to - volume ratio among nanoparticles. These particles were commonly utilized in different biomedical applications drug delivery systems because of their inert existence, mobility, strong dispersion, non-cytototoxicity biocompatibility.